Les Autochtones, le bien-être collectif et la rationalité gouvernementale; une réflexion théorique en forêt publique au Québec. - Denis Blouin; Jean-François Bissonnette; Luc Bouthillier (VertigO)
The rationality of the state at work in the governance of public forests greatly limits the ability of indigenous communities to put new forest models into practice. The findings of the Mi'gmaq of Gespeg's commitment to forestry, as well as the difficulties encountered in implementing their community forest are the starting point for shedding light on the rationality that governs the use of Quebec's public land. This governmental rationality greatly limits the actions that can be taken to meet the needs and aspirations of specific groups. Thus, the system of governmentality, in Foucault's terms, of Quebec public lands is based on a one-dimensional conception of the Quebec population and a homogeneous vision of the territory and the economy. This perspective guides government actions towards the exploitation of resources and the territory based on the well-being of the Quebec population in general. The Aboriginals are therefore on the margins of the exercise of state power over its territory. Indigenous forestry carried out at the local level therefore confronts the mission of the responsible ministries. In addition, the indigenous desire to adapt the public forest management framework to its vision constitutes a challenge for scientific forestry, the basis of state forest management. These indigenous claims are currently exerting strong pressure for a transformation of the governmentality of public lands. Thus, the system of governmentality of public lands is called upon to redefine itself, both in its conception of the Quebec population, of the rights of certain groups, of its vision of the role of public lands, and in its system of knowledge.